Volume 3: Biomedical and Biotechnology Engineering 2015
DOI: 10.1115/imece2015-51836
|View full text |Cite
|
Sign up to set email alerts
|

PMMA in Bone Allograft Fixation Utilizing Unicortical Versus Bicortical Screws: A Finite Element Analysis

Abstract: Bone grafts are widely used in skeletal reconstruction subsequent to tumor surgery, traumatic injuries, or in conjunction with a total joint procedure. As the graft site may be subjected to destabilizing mechanical forces, any motion at the interface between graft and the host tissue may impede or prevent healing. The application and the maintenance of the compression between screw threads and the bone is the most important factor in attaining rigid internal fixation by means of screws or screws & plates. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Biomechanical studies strongly support the use of PMMA in decreasing fracture risk. 11,13 Gupta et al suggested that adding intramedullary cement led to fracture rates of only 4.3%, 1 and Frisoni et al 10 found a lower fracture rate when adding intramedullary cement to their plate fixation. These results contrast the current study, as we did not establish a difference in fracture rates between cemented and noncemented allografts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biomechanical studies strongly support the use of PMMA in decreasing fracture risk. 11,13 Gupta et al suggested that adding intramedullary cement led to fracture rates of only 4.3%, 1 and Frisoni et al 10 found a lower fracture rate when adding intramedullary cement to their plate fixation. These results contrast the current study, as we did not establish a difference in fracture rates between cemented and noncemented allografts.…”
Section: Discussionmentioning
confidence: 99%
“…Holes in an allograft function as stress risers and could contribute to the increased incidence of fracture. [11][12][13] Further study is needed to better characterize this correlation.…”
Section: Figurementioning
confidence: 99%